Máximo valor de la empresa y ADRs - Pacheco Mexzon, Raimundo Renaun (2011)
The globalization of the economy and the internationalization of capital markets today is quite widespread in the world, that is why there is no place for insulation of different markets, including the stock market and in the case of the Peruvian market is no exception to this reality. In this new context exist in the United States of North America, the American Depositary Recipts or ADRs The ADRs are U.S. financial instruments, whose goal is to allow companies from foreign countries may in the New York Stock Exchange (NYSE) put their actions by entering in this way to the market of capitals of the United States of America. Admission to the American capital market, allows companies in foreign countries have new alternatives of business financing or diversification of its shareholders with which expand the borders of their capital markets. This situation is even more favourable for companies in emerging countries with economies sub developed by that allows them to place their actions in financial markets more evolved. The importance that have taken these values in the stock market, suggests that they may be a good alternative of financing for enterprises in countries developing inside of which is the Peru. From there that our concern is to make a simple model for the issuing and placement of ADRs by Peruvian companies will contribute to improving the value of the company. This model allowed calculate appropriate capital structure and achieve increased the value of the company and it was concluded that the ADRs level III and level IV are a good alternative to financing for Peruvian companies seeking to increase their capital and maximizing the market value of the company according to a suitable capital structure.